Problematika Pendamping Desa Profesional dalam Pemberdayaan Masyarakat Desa di Kota Padangsidimpuan - DIANTO, ICOL (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2018)
Professional village facilitators are facilitators who provide assistance to the community. Its presence is the demand of Law Number 6 of 2014 concerning Villages and the regulation of the village minister No. 3 of 2015 concerning Village Assistance. Four years of village funds and village assistance programs are running, but there have not been many changes. This condition is affected by the problems experienced by professional village assistants. This research was conducted in the City of Padangsidimpuan using a qualitative-descriptive method, found four aspects of the problematic professional village assistants. First Quantity Aspect: looking at the problems that arise due to the quantity of available energy factors, there are limited physical abilities of professional village assistants in providing mentoring services and lack of focus on community empowerment activities that can foster community awareness, independence and welfare. Second Quality Aspect: mastery of village facilitators on empowerment, academic material and empowerment theories through formal education and through special education and training. Field findings related to the quality aspect are that there are still professional village assistants with secondary school education, inappropriate scientific background with the field of empowerment and community assistance, lack of education and training, knowledge and mastery of empowerment and community assistance materials, need a process for knowledge internalization. The three aspects of division of labor assistance found that the success of the professional village assistance work program was influenced by the division of labor and the unbalance of workload with the honorarium received. Coordination Aspects means that village technical experts / assistants have not maximally developed coordination relations with local governments so policies to support mentoring programs are not yet available.Â Pendamping desa profesional adalah fasilitator yang melakukan pendampingan kepada masyarakat. Kehadirannya adalah tuntutan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa dan Permendes No 3 Tahun 2015 Tentang Pendampingan Desa. Empat tahun program dana desa dan pendampingan desa berjalan, namun belum banyak perubahan. Kondisi ini dipengaruhi oleh problematika yang dialami oleh pendamping desa profesional. Penelitian ini dilakukan di Kota Padangsidimpuan dengan menggunakan metode kualitatif-deskriptif, ditemukan empat aspek problematika pendamping desa profesional. Pertama Aspek Kuantitas: melihat persoalan-persoalan yang muncul disebabkan oleh faktor kuantitas tenaga yang tersedia ditermukan keterbatasan kemampuan fisik tenaga pendamping desa profesional dalam melakukan pelayanan pendampingan dan kurang fokus kegiatan pemberdayaan masyarakat yang dapat menumbuhkan kesadaran, kemandirian dan kesejahteraan masyarakat. Kedua Aspek Kualitas: penguasaan pendamping desa terhadap materi pemberdayaan, akademis dan teori-teori pemberdayaan melalui pendidikan formal dan melalui pendidikan dan pelatihan khusus. Temuan lapangan terkait aspek kualitas yaitu masih ada pendamping desa profesional berpendidikan sekolah menangah, tidak sesuainya latarbelakang keilmuan dengan bidang kerja pemberdayaan dan pendampingan masyarakat, minimnya pendidikan dan pelatihan, keilmuan dan penguasaan materi pemberdayaan dan pendampingan masyarakat, butuh proses untuk internalisasi pengetahuan. Ketiga Aspek Pembagian Kerja Pendampingan menemukan bahwa kesuksesan program kerja pendampingan desa profesional dipengaruhi oleh pembagian kerja dan ketidakberimbangan beban kerja dengan honor yang diterima. Aspek Koordinasi maksudnya tenaga ahli/pendamping teknis desa belum maksimal membangun hubungan koordinasi dengan pemerintah daerah sehingga kebijkan-kebijakan untuk mendukung program pendampingan belum tersedia.Kata Kunci: Pendamping Desa, Pemberdayaan Masyarakat, Problematika